FAKTOR-FAKTOR YANG BERKONTRIBUSI TERHADAP PERILAKU HERDING PADA INVESTOR SAHAM RITEL DI BURSA EFEK INDONESIA - Zakirullah Zakirullah; Syarifah Rahmawati (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2020)
This research aims to identify various factors that contribute to herding behavior on the Indonesia Stock Exchange. The data in this study uses primary data in the form of a structured questionnaire that is personally sent to respondents. This research focuses on the psychology of retail investors as well as various factors that contribute to herding behavior among retail investors on the Indonesia Stock Exchange. The sampling used a purposive sampling technique conducted on 287 investors or respondents. The analytical method used is factor analysis with the CFA (Confirmatory Factor Analysis) approach. The results of the study show that investors considered various parameters when making their investment decisions. Include the power of intuition, the ability to take risks and the confidence level of retail investors has a greater influence when developing investment strategies. While the results of a factor analysis from 8 herding factors based on the replication of research Saxena et al. (2016), only 3 factors that correspond to the findings of Saxena et al., that is: lack of awareness, under confidence and optimism. Two factors forming herding form the same component (in one component), that is: social proof-bandwagon effect and speculation-volatility in global market. While the factors that do not form herding behavior are reputational factors.